Perencanaan Strategik Sistem Informasi Pengembangan Usaha UD Vier 57 Sehat Bergizi - Fadli, Rizki; Syamsun, Muhammad; Trilaksani, Wini (Institut Pertanian Bogor, 2017)
Small, medium to large companies in the computerization era is required to satisfy the customer needs. The existence of internet allow customer to receive information over the world. internet usage has been used by UD Vier 57 Sehat Bergizi in 2016, but there are no significant impact on production or number of agents. This study has three main objectives that include the following: (1) to identify the implementation of information system in UD Vier 57 Sehat Bergizi, (2) to analyze the needs of information system to improve the company’s competitive advantages and (3) to identify and recommend appropriate business development strategy. Analysis data was used in this study are value chain analysis, five competitive forces porter and SWOT (Strengths, Weakness, Opportunities dan Threats) analysis. Sample that used in this research was 2 respondents. This study showed that the use of information technology in UD Vier 57 Sehat Bergizi is not optimal. IFE score was 3,098 described that the strength owned by UD Vier 57 Sehat Bergizi can overcome it weakness fairly enough. EFE score was 3,339 described that UD Vier 57 Sehat Bergizi was good enough in responding the opportunity and minimize the threat. Score combination of EFE and IFE in IE matrix located in quadrant IV, grow and build. Strategy that fit to UD Vier 57 Sehat Bergizi was intensive strategy (market penetration, market development and product development). SWOT analysis produces 6 alternative strategy formula. Based on calculation in Quantitative Strategic Planning matrix, the most interesting strategy produced was increase marketing intensively and efficiently through online media.